Partisipasi Masyarakat dalam Pembayaran Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Kota Medan - Pane, Muhammad Sorimuda; Revida, Erika; Nasution, Muhammad Arifin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study analyzes community participation in paying the Rural and Urban Land and Building Tax (PBB-P2) in Medan City. It asks: What forms does citizen participation take, what strategies does the municipality deploy to stimulate fiscal engagement, and what obstacles limit participation? A qualitative descriptive design was used, combining in-depth interviews, field observation, and document analysis with informants from the local revenue agency and taxpayers across socio-economic groups. Findings show higher participation in urban neighborhoods due to better information access, stronger tax literacy, and uptake of digital services, while peripheral areas face uneven information distribution, limited access to efficient administrative services, and weak perceptions of tangible benefits. Municipal initiatives—service digitalization, community-based campaigns, and incentives—have yielded positive yet uneven effects, requiring broader reach and more consistent implementation. The study concludes that tax participation reflects the quality of state–citizen relations; sustained, collaborative, and equity-oriented approaches are needed to consolidate compliance and, in turn, strengthen locally generated revenue and inclusive development.‎